Evidence of human leptospirosis cases in a cohort of febrile patients in Bangui, Central African Republic: a retrospective study, 2012–2015 - (:unkn) unknown (My University, 2018)
BACKGROUND: In spite of a local favorable environment, leptospirosis has never been described in Central African Republic so far mainly because of the weakness of diagnostic tests and differential diagnostic strategy for febrile jaundice cases negative for yellow fever virus. Here we bring a complementary insight to conclusions of Gadia CLB et al. regarding the presence of leptospirosis in Central African Republic in YFV-negative febrile icteric patients.METHODS: Our study included 497 individuals presenting with fever and jaundice but negative for yellow fever infection, retrospectively selected from the national surveillance biobank for yellow fever in Institut Pasteur de Bangui, Central African Republic. A combination of serological (ELISA, agglutination) and molecular biology techniques (quantitative real-time polymerase chain reaction) was used to identify Leptospira or the patient's immune response to the bacteria. Statistical analyses were done using the non parametric Mann-Withney U test with a 5% statistical threshold.RESULTS: ELISA test results showed 46 positive serum samples while 445 were negative and 6 remains equivocal. In addition, the reference microscopic agglutination test for leptospirosis diagnostic confirmed that 7 out of 32 samples tested were positive. Unfortunately, all 497 serum samples tested for leptospirosis were negative using the molecular techniques.CONCLUSIONS: Unlike Gadia et al., we confirmed that leptospirosis is circulating in Central African Republic and therefore may be responsible for some of the unexplained cases of febrile jaundice in the country. Thus, leptospirosis needs to be investigated to improve identification of aetiological pathogens. Our study also suggests a need to improve sample transportation and storage conditions.
Keywords: African Research